2021
DOI: 10.1590/1518-8345.5012.3491
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and coping strategies in graduate students in the COVID-19 pandemic

Abstract: Objective: to verify the relation of depression, anxiety, and stress symptoms with coping strategies in graduate students in the context of the new coronavirus pandemic (COVID-19). Method: an electronic cross-sectional and correlational survey was conducted with 331 Brazilian graduate students, aged 20-64 years old, who answered an online form containing a sociodemographic data questionnaire, a coping strategies scale, and the DASS-21 scale. Descriptive analysis, Mann-Whitney U or Kruskal-Wallis tests, and Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
11

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 15 publications
2
9
0
11
Order By: Relevance
“…Additionally, a prior study with Chinese medical students showed that depression and anxiety negatively correlated with positive coping and positively correlated with negative coping 51 . As with medical students in our study, other studies in Brazil showed that undergraduate students from other courses 38 and graduate students 39 with depression, anxiety, and stress were also using more avoidance strategies. Interestingly, both Brazilian medical students and the Brazilian general population were using more avoidance coping strategies during the pandemic period 52 .…”
Section: Interpretation Of Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Additionally, a prior study with Chinese medical students showed that depression and anxiety negatively correlated with positive coping and positively correlated with negative coping 51 . As with medical students in our study, other studies in Brazil showed that undergraduate students from other courses 38 and graduate students 39 with depression, anxiety, and stress were also using more avoidance strategies. Interestingly, both Brazilian medical students and the Brazilian general population were using more avoidance coping strategies during the pandemic period 52 .…”
Section: Interpretation Of Resultssupporting
confidence: 74%
“…The pandemic context seems to contribute to an increase in the overall prevalence of depression and anxiety in undergraduate medical students 10 . Compared with the Brazilian general population 37 and with Brazilian undergraduate students from other courses 38,39 the medical students in this study had much higher prevalence rates of depression, anxiety, and stress symptoms.…”
Section: Interpretation Of Resultsmentioning
confidence: 62%
“…Studies have demonstrated that anxiety impairs learning ability 39,40 . The difference between the learner's performance before (pre-test) and after (post-test) the teacher's intervention is a valuable measure of learning 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…In the current context, the COVID‐19 pandemic has increased this group’s vulnerability to mental illness. Social isolation, abrupt interruption of academic activities, remote teaching, risk of death due to infection, and loss of friends and family may result in psychological suffering, promoting conditions such as reduced sleep quality, anxiety, depression, and stress, among other difficulties arising from the experience of this period of greater emotional mobilisation (Li et al, 2021; Patias et al, 2021; Scorsolini‐Comin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…anxiety, depression, and stress, among other difficulties arising from the experience of this period of greater emotional mobilisation (Li et al, 2021;Patias et al, 2021;Scorsolini-Comin et al, 2021).…”
mentioning
confidence: 99%